4.5 [mu] m ultra-thin lithium battery copper foil prepared with high current density and preparation process thereof
By adopting high -current density preparation process and specific additives in lithium battery and copper foil preparation process, it is difficult to prepare the problem of high quality of 4.5 μm extremely thin lithium battery and copper foil under high -current density in existing technologies, and achieve higher tensile resistance. The intensity and extension rate have improved product quality and production efficiency.
Patent Information
- Application Number
- CN202411504342.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to continuously prepare high-quality 4.5μm extremely thin lithium battery copper foil under high current density, resulting in insufficient copper ions in the solution, copper-poor charred defects in the product, and additives cannot meet customers under high current density conditions. Resistant tensile strength and elongation.
A high current density preparation process is used to improve the copper dissolution efficiency through an immersion microporous copper dissolution device, and collagen, polydisulfide propane sulfonic acid (SPS), polyethylene glycol (PEG) and hydroxyethyl are used in the additive preparation. Cellulose (HEC) is used as an additive, and its concentration is controlled to improve the tensile strength and elongation of lithium battery copper foil.
It achieves the stable preparation of 4.5μm ultra-thin lithium battery copper foil under high current density, improves the tensile strength and elongation, enhances product quality and production efficiency, and reduces production costs.
Smart Images

Figure CN119352111A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery copper foil preparation, and in particular to a 4.5 μm ultra-thin lithium battery copper foil prepared at a high current density and a preparation process thereof. Background Art
[0002] As power batteries move toward higher energy density and new energy vehicle battery systems require lightweight development, lithium battery copper foils are also required to be lighter, more flexible, and safer. That is, the thickness of lithium battery copper foils is required to develop from 8μm to 6μm, or even thinner than 4.5μm. Compared with 8-micron lithium battery copper foils, the use of 6-micron and 4.5-micron lithium battery copper foils can increase the energy density of lithium batteries by 5% and 9% respectively. According to research, it is estimated that by 2025, the domestic demand for 4.5μm copper foil will reach 269,000 tons. Therefore, the key technology for manufacturing 4.5μm ultra-thin lithium battery copper foils is the inevitable direction of industry development.
[0003] When preparing 4.5μm ultra-thin lithium battery copper foil, the precision requirements for the preparation process are very high. In order to obtain high-quality performance and consider preparation stability, most people in the industry use low current density to prepare 4.5μm ultra-thin lithium battery copper foil. However, as the demand increases, the current density needs to be continuously improved to increase production. In the existing preparation process of 4.5μm ultra-thin lithium battery copper foil, copper dissolving liquid preparation is to add copper material into sulfuric acid solution, and improve the dissolution effect of copper wire through oxygen oxidation and steam heating. When the current density of raw foil production reaches 6500A / ㎡, 6 raw foil machines need to consume about 280kg of copper per hour. Under the high amount of precipitated copper, the copper dissolving efficiency is too low, which will make the copper ions in the solution fail to meet the requirements of copper foil production, resulting in the copper-poor "burned" defect of copper foil products; additive preparation is to dissolve different substances in the preparation tank by accurate weighing, and add them to the raw foil manufacturing system quantitatively after the solution is clear and there is no floating matter. The tensile strength and elongation of 4.5μm lithium battery copper foil products produced by conventional additives collagen, SPS, and PEG under high current density conditions cannot meet customer needs; raw foil manufacturing is to supply copper sulfate solution and additives that meet high current density into the raw foil machine to prepare 4.5μm lithium battery copper foil under the action of direct current. Therefore, if we want to continuously produce extremely thin copper foil with excellent quality under high current density and short electrolysis time, further research and development is needed in copper dissolving liquid, additive preparation, raw foil manufacturing, etc. Summary of the invention
[0004] Based on the above, the purpose of the present invention is to provide a process for preparing 4.5μm ultra-thin lithium battery copper foil using high current density, and the 4.5μm ultra-thin lithium battery copper foil prepared by the process.
[0005] To achieve its purpose, the present invention adopts the following technical solution: The present invention provides a process for preparing a 4.5 μm ultra-thin lithium battery copper foil at a high current density, comprising the following steps: Step 1, copper dissolving and liquid preparation: the copper dissolving and liquid preparation is realized by an immersion-type microporous copper dissolving device, which comprises a copper dissolving tower body, wherein an air inlet pipe and a liquid inlet pipe extending longitudinally to the bottom of the copper dissolving tower body are arranged on the top of the copper dissolving tower body; an annular pipe is arranged in the circumferential direction of the bottom of the copper dissolving tower body, and an air inlet pipeline is arranged in the direction of the central axis of the bottom of the copper dissolving tower body; the annular pipeline is communicated with the liquid inlet pipe, and a plurality of holes are evenly distributed on the annular pipeline; the air inlet pipeline is communicated with the air inlet pipe, and a plurality of ventilation membrane tubes with pores of 0.1 μm are evenly distributed vertically on the air inlet pipeline; The copper dissolving liquid preparation comprises placing a copper wire at the bottom of a copper dissolving tower body, introducing compressed air through an air inlet pipe, and the compressed air enters the copper dissolving tower body through the gap on the ventilation membrane tube; self-circulating sulfuric acid is heated by an external system, and then introduced into the copper dissolving tower body through the liquid inlet pipe, and discharged through the holes on the annular pipe, and undergoes an oxidation reaction with the copper wire to generate a copper sulfate solution; Step 2: Preparation of additives Dissolving the leveling agent, brightener, inhibitor and non-ionic active agent in water respectively and mixing them evenly to obtain an additive; Step 3: Raw Foil Manufacturing The prepared copper sulfate solution and additives are mixed to obtain an electrolyte, which is then transported to the foil machine through a pipeline at 6100-6500A / m 2 Electrolysis under high current density can obtain 4.5μm ultra-thin lithium battery copper foil.
[0006] As a further preferred embodiment of the technical solution of the present invention, in step 1, the amount of compressed air used in the immersion microporous copper dissolution device is 400-600 Nm 3 / h, the reaction temperature is 50-60℃, the sulfuric acid self-circulation flow rate is 100-120m³ / h; the copper ion concentration in the immersion microporous copper dissolving device is 130-140g / L, and the copper supplement flow rate is controlled at 1-1.5m 3 / h·unit, the copper ion concentration in the foil machine can be stabilized at 95±5g / L, the electrolyte temperature is 51±1℃, and it can match 8 foil machines at a current density of 6100~6500A / m 2 The amount of copper required to prepare 4.5μm ultra-thin lithium battery copper foil.
[0007] Furthermore, in the additives of step 2, the concentrations of the leveler, brightener, inhibitor and non-ionic active agent are 20-30 mg / L, 10-20 mg / L, 6-8 mg / L and 4-8 mg / L respectively.
[0008] Furthermore, in step 2, the leveling agent A is collagen, the brightening agent B is polydisulfide propane sulfonic acid (SPS), the inhibitor is polyethylene glycol (PEG), and the non-ionic active agent is D-hydroxyethyl cellulose (HEC).
[0009] Furthermore, in step 3, the electrolyte flow rate is 60-80m 3 / h.
[0010] The high current density preparation process can be used to prepare a 4.5 μm ultra-thin lithium battery copper foil with a tensile strength of 33 to 38 kgf / mm. 2 , the elongation is 6~8%.
[0011] By adopting the above technical solution, the beneficial effects of the present invention are: 1. The present invention adopts a high current density preparation process to prepare a 4.5μm ultra-thin lithium copper foil, which increases the preparation load and has a high copper dissolving efficiency. At the same time, the prepared 4.5μm ultra-thin lithium copper foil has simple additive types, which is more conducive to on-site regulation than the composite additives containing 5 or more additive types in the prior art, making the quality of the produced lithium copper foil more stable, and can effectively improve the energy density of lithium-ion batteries. In addition, the additives involved in the present invention are all domestic additives, which are easy to obtain and low in price, which is conducive to reducing production costs.
[0012] 2. The additive preparation step of the present invention includes using collagen A as a leveling agent, polydisulfide propane sulfonic acid (SPS) as a brightener, polyethylene glycol (PEG) as an inhibitor, and hydroxyethyl cellulose (HEC) as a non-ionic active agent. The concentrations of A, B, C, and D are controlled at 20-30 mg / L, 10-20 mg / L, 6-8 mg / L, and 4-8 mg / L, respectively. Among them, collagen A is ionized into cations during the deposition process, gradually moves to the cathode, adsorbs and discharges with electrophoresis. When the cathode adsorbs collagen and accumulates to a certain amount, it will increase the resistance, inhibit the precipitation of copper ions, and play a role in inhibiting the deposition of copper ions. Polydisulfide propane sulfonic acid (SPS) B acts on the copper ions in the copper foil, and its concentration change will directly cause the copper foil structure to develop from a cone to a layered shape, which helps to reduce the roughness of the copper foil surface, improve the tensile strength and elongation, effectively inhibit the pinhole problem, and play the role of a leveling agent and a brightener. Agent C, polyethylene glycol (PEG), helps to strengthen the cathode polarization phenomenon, reduce the surface roughness of copper foil, and inhibit the electrodeposition of impurity metals, but its excessive use will also lead to a decrease in the tensile strength and elongation of copper foil. Therefore, the concentration is controlled at 6-8 mg / L. As a non-ionic surfactant, D, hydroxyethyl cellulose (HEC) can keep the grains growing horizontally, reduce the surface roughness of copper foil, inhibit pinholes, and improve its tensile strength and elongation. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a structural schematic diagram of an immersion-type microporous copper dissolving device in the preparation process of the present invention; Figure 2 It is a schematic structural diagram of the bottom of the copper dissolving tower body in the immersion-type microporous copper dissolving device of the present invention; Figure numerals: 1-air inlet pipe; 2-liquid inlet pipe; 3-air inlet pipeline; 4-membrane tube; 5-copper dissolving tower body; 6, annular pipeline. DETAILED DESCRIPTION
[0014] In order to facilitate understanding by those skilled in the art, the present invention is further described below in conjunction with examples. The examples are only preferred embodiments of the present invention and are not intended to limit the present invention. All other examples obtained by those of ordinary skill in the art based on the following examples without creative work are within the scope of protection of the present invention.
[0015] The preparation process provided by the present invention sequentially comprises the steps of dissolving copper to prepare liquid, preparing additives and manufacturing raw foil.
[0016] The copper dissolving liquid is realized by an immersion-type microporous copper dissolving device, which includes a copper dissolving tower body 5, wherein an air inlet pipe 1 and a liquid inlet pipe 2 are longitudinally provided at the top of the copper dissolving tower body 5 and extend to the bottom of the copper dissolving tower body 5; an annular pipe 6 is circumferentially provided at the bottom of the copper dissolving tower body 5, and an air inlet pipeline 3 is provided in the direction of the central axis of the bottom of the copper dissolving tower body 5; the annular pipeline 6 is communicated with the liquid inlet pipe 2, and a plurality of holes are evenly distributed on the annular pipeline 6; the air inlet pipeline 3 is communicated with the air inlet pipe 1, and a plurality of ventilation membrane tubes 4 with a pore size of 0.1 μm are vertically evenly distributed on the air inlet pipeline 3; The copper dissolving liquid preparation method comprises placing a copper wire at the bottom of a copper dissolving tower body 5, and introducing compressed air through an air inlet pipe 1, and the compressed air enters the copper dissolving tower body 5 through the gap on the ventilation membrane tube 4; the sulfuric acid is self-circulated and heated by an external system, and then introduced into the copper dissolving tower body 5 through the liquid inlet pipe 2, and discharged through the holes on the annular pipe 6, and undergoes an oxidation reaction with the copper wire to generate a copper sulfate solution.
[0017] Compared with the conventional copper dissolving method, the present invention adopts a vent membrane tube 4 with a pore size of 0.1 μm as the air path for the compressed air to be blown in. The vent membrane tube 4 is a polypropylene membrane tube with acid resistance, temperature resistance and pressure resistance. The vent membrane tube 4 is evenly distributed and fixed at the bottom of the copper dissolving tower body 5, and the bubbles are dispersed into the copper dissolving tower body 5 by using the micropores of the membrane tube. At the same time, the sulfuric acid after external self-circulation heating is transported to the bottom of the copper dissolving tower body 5 through the liquid inlet pipe 2. An annular pipe 6 is provided at the bottom of the tower body, and holes with a diameter of φ8 are opened on the pipe wall. The total area of the holes is consistent with the cross-sectional area of the annular pipe 6, so that oxygen and sulfuric acid can be uniformly and alternately contacted with metallic copper, so that the copper in the copper dissolving tower body 5 can participate in the dissolution reaction.
[0018] Among them, when the current density of raw foil preparation reaches 6500A / ㎡, 8 raw foil machines need to consume about 280kg of copper per hour. Under the condition of high copper precipitation, the efficiency of copper dissolving and liquid preparation is one of the key factors affecting the preparation of 4.5μm lithium copper foil. If the copper dissolving efficiency is too low, the copper ions in the solution will not meet the requirements of copper foil preparation, resulting in the defect of copper foil being poor in copper and "burned". The copper dissolving and liquid preparation of lithium copper foil is to add copper material to sulfuric acid, and achieve the effect of copper dissolving through oxygen oxidation and steam heating. When a small amount of copper material is added, the copper ion standard required for preparation cannot be met. When a large amount of copper material is added, copper material accumulation will be caused. At the same time, no matter how large the amount of oxygen in the compressed air is, it cannot fully contact and oxidize with the copper material, affecting the copper dissolving efficiency. Therefore, using less copper material and lower energy to continuously, uniformly and stably provide copper sulfate solution for raw foil manufacturing at a higher efficiency is the key to preparing lithium copper foil.
[0019] The copper dissolving and liquid preparation steps of the present invention can effectively match the copper quantity required by the system with a current density of 6100-6500A / ㎡·unit-hour for 8 raw foil machines. The compressed air consumption of the developed immersion microporous copper dissolving equipment is controlled at 400-600Nm 3 / h, temperature 50 ~ 60 ℃, sulfuric acid self-circulation flow 100 ~ 120m³ / h, the copper ion in the copper dissolving tank can be stabilized at about 130 ~ 140g / L, the copper ion in the raw foil supply liquid can be stabilized at 95 ± 1g / L, and the copper supplement flow rate can be controlled at 1-1.5m 3 / h·unit, the copper ion in the raw foil supply solution can be stabilized at 95±5g / L.
[0020] The additive preparation steps include using collagen A as a leveling agent, polydisulfide propane sulfonic acid (SPS) as a brightening agent, polyethylene glycol (PEG) as an inhibitor, and hydroxyethyl cellulose (HEC) as a non-ionic active agent, and the concentrations of A, B, C, and D are controlled at 20-30 mg / L, 10-20 mg / L, 6-8 mg / L, and 4-8 mg / L, respectively.
[0021] The raw foil manufacturing step includes mixing the prepared copper sulfate solution and additives to obtain an electrolyte, and the electrolyte is transported to the raw foil machine through a pipeline for electrolysis, and the current density is controlled to be 6100-6500A / m 2 , to produce an extremely thin 4.5μm lithium copper foil. In this step, the flow rate of the electrolyte is 60-80m 3 / h.
[0022] In the above process, the factors affecting the quality of copper foil include: 2+ content, H2SO4 content, copper sulfate solution temperature, copper sulfate solution flow rate, current density, and additives.
[0023] The present invention lists the following examples to illustrate the preparation process: Example 1 The preparation process provided in this embodiment includes, in sequence, a copper dissolving and liquid preparation step, an additive preparation step, and a raw foil manufacturing step.
[0024] The copper dissolving and liquid preparation step includes using a copper wire to perform an oxidation reaction through an immersion-type microporous copper dissolving device to generate a copper sulfate solution.
[0025] The copper dissolving rate is generally proportional to the air volume. The compressed air volume for copper dissolving is 400Nm 3 / h, reaction temperature 50℃, sulfuric acid self-circulation flow rate 100m³ / h, copper ions in the copper dissolving tower body 5 are 130g / L.
[0026] Control the copper supply flow rate to 1m 3 / h·unit, the copper ion in copper sulfate in the foil machine can be controlled at 95g / L.
[0027] The additive preparation steps include adding agent A collagen as a leveling agent, agent B polydisulfide propane sulfonic acid (SPS) as a brightening agent, agent C polyethylene glycol (PEG) as an inhibitor, and agent D hydroxyethyl cellulose (HEC) as a non-ionic active agent; wherein the concentrations of agents A, B, C, and D are controlled at 20 mg / L, 10 mg / L, 6 mg / L, and 4 mg / L, respectively.
[0028] The raw foil manufacturing process includes mixing the prepared copper sulfate solution and additives to obtain an electrolyte, which is then transported to the raw foil machine through a pipeline for electrolysis. The electrolyte flow rate is controlled at 80m 3 / h, current density is 6100A / m 2 , producing an extremely thin 4.5μm lithium battery copper foil.
[0029] The tensile strength of the 4.5 μm lithium battery copper foil prepared in this embodiment is 33.5 kgf / mm 2 , the elongation is 6.5%.
[0030] Example 2 The preparation process provided in this embodiment includes, in sequence, a copper dissolving and liquid preparation step, an additive preparation step, and a raw foil manufacturing step.
[0031] The copper dissolving and liquid preparation step includes using a copper wire to perform an oxidation reaction through an immersion-type microporous copper dissolving device to generate a copper sulfate solution.
[0032] The copper dissolving rate is generally proportional to the air volume. The compressed air volume for copper dissolving is 800Nm 3 / h, reaction temperature 55℃, sulfuric acid self-circulation flow rate 110m³ / h, copper ions in copper dissolving tower body 5 are 135g / L.
[0033] Control the copper filling flow rate at 1.3m 3 / h·unit, the copper ion in copper sulfate in the foil machine can be controlled at 98g / L.
[0034] The additive preparation steps include adding agent A collagen as a leveling agent, agent B polydisulfide propane sulfonic acid (SPS) as a brightening agent, agent C polyethylene glycol (PEG) as an inhibitor, and agent D hydroxyethyl cellulose (HEC) as a non-ionic active agent; wherein the concentrations of agents A, B, C, and D are controlled at 25 mg / L, 15 mg / L, 7 mg / L, and 6 mg / L, respectively.
[0035] The raw foil manufacturing process includes mixing the prepared copper sulfate solution and additives to obtain an electrolyte, which is then transported to the raw foil machine through a pipeline for electrolysis. The electrolyte flow rate is controlled at 70m 3 / h, current density is 6300A / m 2 , producing an extremely thin 4.5μm lithium battery copper foil.
[0036] The tensile strength of the 4.5 μm lithium battery copper foil prepared in this embodiment is 35.5 kgf / mm 2 , the elongation is 7%.
[0037] Example 3 The preparation process provided in this embodiment includes, in sequence, a copper dissolving and liquid preparation step, an additive preparation step, and a raw foil manufacturing step.
[0038] The copper dissolving and liquid preparation step includes using a copper wire to perform an oxidation reaction through an immersion-type microporous copper dissolving device to generate a copper sulfate solution.
[0039] The copper dissolving rate is generally proportional to the air volume. The compressed air volume for copper dissolving is 600Nm 3 / h, reaction temperature 60℃, sulfuric acid self-circulation flow rate 120m³ / h, copper ions in copper dissolving tower body 5 are 140g / L.
[0040] Control the copper supply flow rate at 1.5m 3 / h·unit, the copper ion in copper sulfate in the foil machine can be controlled at 100g / L.
[0041] The additive preparation steps include adding agent A collagen as a leveling agent, agent B polydisulfide propane sulfonic acid (SPS) as a brightening agent, agent C polyethylene glycol (PEG) as an inhibitor, and agent D hydroxyethyl cellulose (HEC) as a non-ionic active agent; wherein the concentrations of agents A, B, C, and D are controlled at 30 mg / L, 20 mg / L, 8 mg / L, and 8 mg / L, respectively.
[0042] The raw foil manufacturing process includes mixing the prepared copper sulfate solution and additives to obtain an electrolyte, which is then transported to the raw foil machine through a pipeline for electrolysis. The electrolyte flow rate is controlled at 60m3 / h, current density is 6500A / m 2 , producing an extremely thin 4.5μm lithium battery copper foil.
[0043] The performance parameters of the 4.5μm lithium battery copper foil prepared in this example are as follows: tensile strength 37.5kgf / mm 2 , elongation 7.5%.
[0044] The above-described implementation methods do not constitute a limitation on the protection scope of the technical solution. Any modification, equivalent replacement and improvement made within the spirit and principle of the above-described implementation methods shall be included in the protection scope of the technical solution.
Claims
1. A process for preparing 4.5 μm ultra-thin lithium battery copper foil at high current density, characterized in that: The process comprises the following steps: Step 1, copper dissolving and liquid preparation: the copper dissolving and liquid preparation is achieved by an immersion type microporous copper dissolving device; The immersion-type microporous copper dissolving device comprises a copper dissolving tower body (5), wherein the top of the copper dissolving tower body (5) is provided with an air inlet pipe (1) and a liquid inlet pipe (2) extending longitudinally to the bottom of the copper dissolving tower body (5); an annular pipe (6) is provided in the circumferential direction of the bottom of the copper dissolving tower body (5), and an air inlet pipeline (3) is provided in the direction of the central axis of the bottom of the copper dissolving tower body (5); the annular pipeline (6) is communicated with the liquid inlet pipe (2), and a plurality of holes are evenly distributed on the annular pipeline (6); the air inlet pipeline (3) is communicated with the air inlet pipe (1), and a plurality of ventilation membrane tubes (4) with a pore size of 0.1 μm are evenly distributed vertically on the air inlet pipeline (3); The copper dissolving liquid preparation method comprises placing a copper wire at the bottom of a copper dissolving tower body (5), and introducing compressed air through an air inlet pipe (1), and the compressed air enters the copper dissolving tower body (5) through the gap on the ventilation membrane tube (4); self-circulating sulfuric acid is heated by an external system, and then introduced into the copper dissolving tower body (5) through a liquid inlet pipe (2), and discharged through holes on a ring pipe (6), and undergoes an oxidation reaction with the copper wire to generate a copper sulfate solution; Step 2: Preparation of additives Dissolving the leveling agent, brightener, inhibitor and non-ionic active agent in water respectively and mixing them evenly to obtain an additive; Step 3: Raw Foil Manufacturing The prepared copper sulfate solution and additives are mixed to obtain an electrolyte, which is then transported to the foil machine through a pipeline at 6100-6500A / m 2 Electrolysis under high current density can obtain 4.5μm ultra-thin lithium battery copper foil.
2. The process for preparing 4.5 μm ultra-thin lithium battery copper foil at high current density according to claim 1, characterized in that: In step 1, the compressed air usage in the immersion microporous copper dissolution device is 400-600 Nm 3 / h, the reaction temperature is 50-60℃, the sulfuric acid self-circulation flow rate is 100-120m³ / h; the copper ion concentration in the immersion microporous copper dissolving device is 130-140g / L, and the copper supplement flow rate is controlled at 1-1.5m 3 / h·unit, the copper ion concentration in the foil machine can be stabilized at 95±5g / L, the electrolyte temperature is 51±1℃, and it can match 8 foil machines at a current density of 6100~6500A / m 2 The amount of copper required to prepare 4.5μm ultra-thin lithium battery copper foil.
3. The process for preparing 4.5 μm ultra-thin lithium battery copper foil at high current density according to claim 2, characterized in that: In the additives of step 2, the concentrations of leveling agent, brightener, inhibitor and non-ionic active agent are 20-30 mg / L, 10-20 mg / L, 6-8 mg / L and 4-8 mg / L respectively.
4. The process for preparing 4.5 μm ultra-thin lithium battery copper foil at high current density according to claim 1, characterized in that: In step 2, the leveling agent is collagen, the brightening agent is agent B polydisulfide propane sulfonic acid (SPS), the inhibitor is polyethylene glycol (PEG), and the non-ionic active agent is D-hydroxyethyl cellulose (HEC).
5. The process for preparing 4.5 μm ultra-thin lithium battery copper foil at high current density according to claim 3, characterized in that: In step 3, the electrolyte flow rate is 60-80m 3 / h.
6. An ultra-thin lithium battery copper foil of 4.5 μm prepared by the high current density preparation process as described in any one of claims 1 to 5.
7. The 4.5 μm ultra-thin lithium battery copper foil prepared by a high current density preparation process as claimed in claim 6, characterized in that: The tensile strength of the ultra-thin electrolytic copper foil is 33-38 kgf / mm 2 , the elongation is 6~8%.